2011
DOI: 10.1177/0961203311404914
|View full text |Cite
|
Sign up to set email alerts
|

Clinical presentations and molecular basis of complement C1r deficiency in a male African–American patient with systemic lupus erythematosus

Abstract: Homozygous deficiencies of early components for complement activation are among the strongest genetic risk factors for human systemic lupus erythematosus (SLE). Eleven cases of C1r deficiency are documented but this is the first report on the molecular basis of C1r deficiency. The proband is an African-American male who developed SLE at 3 months of age. He had a discoid lupus rash and diffuse proliferative glomerulonephritis. Serum complement analysis of the patient showed zero CH50 activity, undetectable C1r,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 49 publications
1
15
0
Order By: Relevance
“…This is the second report of a novel high‐penetrance mutation in C1R as the cause of monogenic and familial SLE. The C1r‐deficient patients in the present study are phenotypically similar to the previously reported patient with this C1r deficiency (see Supplementary Table 2, available on the Arthritis & Rheumatology web site at http://onlinelibrary.wiley.com/doi/10.1002/art.40158/abstract).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This is the second report of a novel high‐penetrance mutation in C1R as the cause of monogenic and familial SLE. The C1r‐deficient patients in the present study are phenotypically similar to the previously reported patient with this C1r deficiency (see Supplementary Table 2, available on the Arthritis & Rheumatology web site at http://onlinelibrary.wiley.com/doi/10.1002/art.40158/abstract).…”
Section: Discussionsupporting
confidence: 85%
“…Biallelic loss‐of‐function mutations in C1S have been found in patients with lupus, but also in asymptomatic individuals . Thus far, a loss‐of‐function mutation causing complete C1r deficiency has been reported in only a single individual: a male patient of African American ancestry who developed symptoms at the age of 3 years .…”
mentioning
confidence: 99%
“…Human subjects with a homozygous genetic deficiency in any of the early components of the classical pathway of complement activation, including C1q, C1r, C1s, and C4 (details in Supplementary Figure 1, available on the Arthritis & Rheumatology web site at http://onlinelibrary.wiley.com/doi/10.1002/art.39589/abstract), almost always develop SLE, regardless of race, sex, or HLA haplotype . Under susceptible backgrounds, mice with genetic knockout of complement C4 or C1q will manifest lupus‐like phenotypes with high titers of antinuclear antibodies (ANAs) and anti‐dsDNA, and a high frequency of glomerulonephritis .…”
mentioning
confidence: 99%
“…67,68 Similarly a number of mutations responsible for C1r deficiency have been identified. 69 However, 7 of the first 12 patients with C1r deficiency were of Puerto Rican descent, suggesting they may be the descendants of a single individual who carried the mutation. 70…”
Section: Molecular Geneticsmentioning
confidence: 99%
“…69,106 The deficiency appears to be inherited in an autosomal recessive fashion. The activity of the classical pathway was either normal or slightly below normal.…”
Section: Pathogenesismentioning
confidence: 99%